ENGARUH PROFITABILITAS, STRUKTUR KEPEMILIKAN DAN AKTIVITAS CORPORATE SOCIAL RESPONSIBILITY TERHADAP AGRESIVITAS PAJAK - Eva Christin S. Simanjuntak (2017)
This research aims to analyze and get empirical evidence about the effect of profitability, ownership institutional, corporate social responsibility on the tax aggressiveness. Samples consist of manufacturing companies listed in Indonesia Stock Exchange (BEI) in the period from 2014-2016. Sampel of the research are 45 companies with 3 years observation that acquired by purposive sampling method. Hypotesys in this research were tested by multiple regression model. The result of this research showed that profitability has a significant effect on tax aggressiveness, but ownership institutional, corporate social responsibility has no effect on tax aggressiveness.